2012
DOI: 10.1007/s10040-012-0854-2
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater pumping by heterogeneous users

Abstract: Journal articleIFPRI3; ISI; CRP2; GRP23MTID; PIMPRCGIAR Research Program on Policies, Institutions, and Markets (PIM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Like Bredehoeft and Young [1970], the authors suggested that part or all of the tax revenue should be rebated to the agents and then question the feasibility of such a scenario. However, Blanco-Gutierrez et al [2011] notes that the efficacy of water use quotas are reduced by high monitoring costs (similar to the tax policy) and Saak and Peterson [2012] show that a uniform quota may also result in unevenly distributed welfare gains among farmers. In addition, the cost that the farmer faces due to this constraint will be borne out in terms of the possible losses due to less water use, especially in drought years.…”
Section: Background On Groundwater Policy (Taxes Versus Quotas)mentioning
confidence: 99%
“…Like Bredehoeft and Young [1970], the authors suggested that part or all of the tax revenue should be rebated to the agents and then question the feasibility of such a scenario. However, Blanco-Gutierrez et al [2011] notes that the efficacy of water use quotas are reduced by high monitoring costs (similar to the tax policy) and Saak and Peterson [2012] show that a uniform quota may also result in unevenly distributed welfare gains among farmers. In addition, the cost that the farmer faces due to this constraint will be borne out in terms of the possible losses due to less water use, especially in drought years.…”
Section: Background On Groundwater Policy (Taxes Versus Quotas)mentioning
confidence: 99%
“…Several studies on the economics of groundwater management have moved away from the representative farmer framework introduced by Gisser and Sanchez (1980). These studies (Feinerman and Knapp, 1983;Saak and Peterson, 2012;Guilfoos et al, 2016) have considered different sources of heterogeneity among producers, including land size and crop type, and have shown that different aquifer management policies could have different cost-effectiveness and distributional effects. Hrozencik et al (2017) introduce well capacity as a source of heterogeneity in a hydro-economic framework.…”
Section: Introductionmentioning
confidence: 99%
“…The single-cell model can be criticized for its strong assumptions about hydrology, which do not accord with the spatial heterogeneity and the slow rates of lateral flow observed in many aquifers (Saak and Peterson, 2012). Recent literature has relaxed the assumptions of instantaneous lateral flow and spatial uniformity (Gaudet et al 2001, Xabadia et al 2004…”
Section: Conceptual Frameworkmentioning
confidence: 99%